The PKGIα–Rac1 pathway is a novel regulator of insulin‐dependent glucose uptake in cultured rat podocytes. Issue 6 (26th November 2020) - Audzeyenka, Irena; Rogacka, Dorota; Rachubik, Patrycja; Typiak, Marlena; Rychłowski, Michał; Angielski, Stefan; Piwkowska, Agnieszka
Abstract: Insulin plays a major role in regulating glucose homeostasis in podocytes. Protein kinase G type Iα (PKGIα) plays an important role in regulating glucose uptake in these cells. Rac1 signaling plays an essential role in the reorganization of the actin cytoskeleton and is also essential for insulin‐stimulated glucose transport. The experiments were conducted using primary rat podocytes. We performed western blot analysis, evaluated small GTPases activity assays, measured radioactive glucose uptake, and performed immunofluorescence imaging to analyze the role of PKGIα‐Rac1 signaling in regulating podocyte function. We also utilized a small‐interfering RNA‐mediated approach to determine the role of PKGIα and Rac1 in regulating glucose uptake in podocytes. The present study investigated the influence of the PKGI pathway on the insulin‐dependent regulation of activity and cellular localization of small guanosine triphosphatases in podocytes. We found that the PKGIα‐dependent activation of Rac1 signaling induced activation of the PAK/cofilin pathway and increased insulin‐mediated glucose uptake in podocytes. The downregulation of PKGIα or Rac1 expression abolished this effect. Rac1 silencing prevented actin remodeling and GLUT4 translocation close to the cell membrane. These data provide evidence that PKGIα‐dependent activation of the Rac1 signaling pathways is a novel regulator of insulin‐mediated glucose uptake in cultured rat podocytes. Abstract : Proposed mechanism of the regulation of insulin‐dependent glucose uptake through the PKGIα–Rac1 pathway in cultured rat podocytes. PKGIα signaling may be required for maintaining glucose homeostasis in podocytes PKGIα regulates cytoskeleton remodeling through activation of PAK/cofilin signaling Downregulation of Rac1 expression abolishes PKGIα‐mediated glucose uptake